PERBANDINGAN METODE PRELOADING DENGAN VAKUM KONSOLIDASI TANAH PADA PEMODELAN DI LABORATORIUM - Ahmad Yasin Al Harits; Istiatun Istiatun (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2021)
ABSTRACT This study aims to determine the parameter comparison of the magnitude of the primary reduction and consolidation time in the preloading method using PVD and vacuum method using PVD with modeling in the laboratory. The benefit of this research is that it can provide a comparison of the preloading method and the vacuum method in terms of accelerating the consolidation time as well as contributing to science in the field of soil improvement. Primary consolidation theory is used in this research. Quantitative descriptive research method with testing data collection techniques by means of modeling in the laboratory. The modeling of the vacuum method used a test tub measuring (1.2 × 0.6 × 0.9) m, the vacuum pump suction capacity of 5 Pa, the air hose as PHD and geomembrane cloth as PVD material. The preloading method with PVD uses a test tub measuring (0.8 × 0.6 × 0.9) m, preloading load in the form of bangka sand (ɣ = 1.532 t / m³) with a thickness of 10 cm and a geomembrane cloth as PVD material. In each test basin filled with soil and water with a soil volume weight of 1.3 t / m³, a ground surface height of 0.5 m and a groundwater level of 0.42 m. The results showed that with the same amount of reduction, namely 7.26 mm preloading method using PVD took 81 hours while in the vacuum method the time needed was 41 hours. Thus it can be concluded that the reduction in the vacuum method is faster than the preloading method with PVD. Keywords: Primer settelment, PVD, Vacum, consolidation time